National report on the status of women in Anguilla - Banks-Devonish, M. Linda...[et al] ([The Consultants] [The Valley]AI, 1994)
Looks at the situation in the early eighties and changes since then. Reviews and appraises international support and focuses on future strategic goals and objectives and correponding financial arrangements.